Development of the Biopen: a handheld device for surgical printing of adipose stem cells at a chondral wound site. (22nd March 2016) - O'Connell, Cathal D; Di Bella, Claudia; Thompson, Fletcher; Augustine, Cheryl; Beirne, Stephen; Cornock, Rhys; Richards, Christopher J; Chung, Johnson; Gambhir, Sanjeev; Yue, Zhilian; Bourke, Justin; Zhang, Binbin; et al.
Abstract: We present a new approach which aims to translate freeform biofabrication into the surgical field, while staying true to the practical constraints of the operating theatre. Herein we describe the development of a handheld biofabrication tool, dubbed the 'biopen', which enables the deposition of living cells and biomaterials in a manual, direct-write fashion. A gelatin–methacrylamide/hyaluronic acid–methacrylate (GelMa/HAMa) hydrogel was printed and UV crosslinked during the deposition process to generate surgically sculpted 3D structures. Custom titanium nozzles were fabricated to allow printing of multiple ink formulations in a collinear (side-by-side) geometry. Independently applied extrusion pressure for both chambers allows for geometric control of the printed structure and for the creation of compositional gradients. In vitro experiments demonstrated that human adipose stem cells maintain high viability (>97%) one week after biopen printing in GelMa/HAMa hydrogels. The biopen described in this study paves the way for the use of 3D bioprinting during the surgical process. The ability to directly control the deposition of regenerative scaffolds with or without the presence of live cells during the surgical process presents an exciting advance not only in the fields of cartilage and bone regeneration but also in other fields where tissue regeneration and replacement are critical.